Applicability of Peleg’s equation in predicting water absorption during the soaking of Ofada and Nerica (L1) rice - Adesina, B S; Olayanju, T M A; Dairo, O U; Bolaji, B O; Sobukola, O P (Journal of Postharvest Technology, 2017)
Water absorption kinetics of Ofada and Nerica (L1) paddy grains were investigated by soaking in water at different temperatures in a  thermostatically controlled water bath at soaking times ranging from 40 to 180 min. Soaking temperatures were obtained from the  gelatinization temperature measured with a Rapid Visco Analyzer (RVA) prior to soaking. Data obtained were fitted to the Peleg Model to  determine Peleg’s constants using a non-linear regression model. Complete gelatinization occurred at 54 °C and 65 °C for Ofada and Nerica  respectively. Soaking temperature selected ranged from 40 to 70oC. The coefficients of determination (R2) for the regression ranged from 0.90  to 0.99 and 0.89 to 0.98 for Ofada and Nerica rice respectively, indicating a good fit to the experimental data. Temperature, time and rice type  had significant effect (p < 0.05) on water absorption. Peleg’s rate constant, (K1) varied proportionally with temperature for both grains while  capacity constant (K2) was not significantly affected by increased temperature for Ofada but decreased with increased temperature for Nerica  paddy. Activation Energy, Ea of 0.42 kJ/mol and 1.78 kJ/mol were obtained for Ofada and Nerica respectively. The soaking parameters  obtained can be use to optimize and characterize soaking conditions and predict water absorption as a function of time and temperature.
Keywords: Absorption; Nerica; Ofada; Paddy; Soaking